If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + -7y = 10 Solving -6x + -7y = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7y' to each side of the equation. -6x + -7y + 7y = 10 + 7y Combine like terms: -7y + 7y = 0 -6x + 0 = 10 + 7y -6x = 10 + 7y Divide each side by '-6'. x = -1.666666667 + -1.166666667y Simplifying x = -1.666666667 + -1.166666667y
| .50x+.45(50)=27.5 | | 4n+2=6(0.333n-0.666n) | | 8x+1=100 | | -5(4n+4)+5n=-80 | | 70=a+(a-36) | | 4(20-0.5y)-2y=150 | | 9x+11=x+4 | | (3x-2)^(5/3)=6 | | 4x-2(-0.5y)=120 | | -5(4n+4)+5n=80 | | 17x+3x+15x+21+4=87 | | -5(4n+4)+5n= | | x^2+6x+9=26 | | 12t-8m=-52 | | 4.2+4=3x+9.4 | | (3x-9)/(x-4) | | -250x-3= | | b-7/4= | | B-7/4 | | 9(x+8)+12=8(x+8)10 | | x6/x3= | | 3.5=-7y+21 | | 9(x+8)*12=8(x+8)+10 | | (10+10)x+x=2 | | 21+3x+1=57 | | 14(8+12)= | | f(x)=-x^2-4x-8 | | -m+12=-9 | | (4a+3)-8=4+2a | | log*5*(x-4)=-1 | | 3/7=4/8 | | 1.5(10w+20)=3+2w |